The influence of a single bout of aerobic exercise on short-interval intracortical excitability - Smith, Ashleigh E.; Goldsworthy, Mitchell R.; Garside, Tessa; Wood, Fiona M.; Ridding, Michael C. (Experimental brain research, 2014)
Regular physical activity can have positive effects on brain function and plasticity. Indeed, there is some limited evidence that even a single bout of exercise may promote plasticity within the cortex. However, the mechanisms by which exercise acutely promotes plasticity are not clear. To further explore the effects of acute exercise on cortical function, we examined whether a single bout of exercise was associated with changes in cortical excitability and inhibition. Using standard techniques, cortical stimulus–response curves [90 % resting motor threshold (RMT)–150 % RMT] were investigated in nine subjects (four females, 31.1 ± 11.7 years) and short-interval intracortical inhibition (SICI) [interstimulus interval 2 ms and 3 ms, conditioning intensities of 80 % active motor threshold (AMT) and 90 % AMT] in 13 subjects (six females, 28.4 ± 5.1 years) before and at 0 and 15 min following 30 min of ergometer cycling at low–moderate or moderate–high intensity. There were no changes in cortical excitability following exercise but less SICI at both 0 and 15 min post-exercise ( F [2, 24] = 7.7, P = 0.003). These findings show that a short period of exercise can transiently reduce SICI. Such a change in inhibition after exercise may contribute to the development of a cortical environment that would be more optimal for plasticity and may partially explain previous findings of enhanced neuroplasticity following low-intensity exercise.